2019
DOI: 10.1017/wsc.2019.50
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of arbuscular mycorrhizal fungi in relation to root colonization, spore density, and soil properties among different spreading stages of the exotic plant threeflower beggarweed (Desmodium triflorum) in aZoysia tenuifolialawn

Abstract: Weed invasion is a prevailing problem in modestly managed lawns. Less attention has been given to the exploration of the role of arbuscular mycorrhizal fungi (AMF) under different invasion pressures from lawn weeds. We conducted a four-season investigation into a Zoysia tenuifolia Willd. ex Thiele (native turfgrass)–threeflower beggarweed [Desmodium triflorum (L.) DC.] (invasive weed) co-occurring lawn. The root mycorrhizal colonizations of the two plants, the soil AM fungal communities and the spore densities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
1
4
0
1
Order By: Relevance
“…The low spore density could be due to the season of soil sampling, which was winter when all the climatic conditions are unfavourable, especially precipitation. The results of this study are also in agreement with the findings of Han et al (2019), which showed that the fungal spore density was low in spring, increased in summer, reached its highest level in autumn and then decreased in winter. The AMF frequency is based on seasonal changes and host metabolic pathway (Yang et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The low spore density could be due to the season of soil sampling, which was winter when all the climatic conditions are unfavourable, especially precipitation. The results of this study are also in agreement with the findings of Han et al (2019), which showed that the fungal spore density was low in spring, increased in summer, reached its highest level in autumn and then decreased in winter. The AMF frequency is based on seasonal changes and host metabolic pathway (Yang et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Other plants invaded the experimental site during the long-term planting process which could affect ryegrass and AMF in the substrates. Secondly, correlations among soil properties, spore densities, and mycorrhizal colonisations were more pronounced in the higher coverage levels 35 . Although annual ryegrass seeds were broadcasted at 20–30 g m −2 , the actual coverage level was not reached the seeding density.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to sludge, there are some factors that may affect the growth of AMF in our research. Firstly, weed invasion is a prevailing problem in modestly managed lawns 35 . Other plants invaded the experimental site during the long-term planting process which could affect ryegrass and AMF in the substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the co-cultivation of maize and sorghum generated interspecific competition between the host plants. This might have induced AMF sporulation in the pots since the density of AMF spores below ground is consistent with the intensity of interspecific competition among invasive and native plants above ground [ 64 ].…”
Section: Discussionmentioning
confidence: 99%